Mechanical and morphological properties of luffa/carbon fiber reinforced hybrid composites. (2020) - Ashok, K.G.; Kalaichelvan, K.; Elango, V.; Damodaran, Ajith; Gopinath, B.; Raju, M.
Abstract: This study investigates the mechanical performance and highlights the failure mechanisms of luffa/carbon fiber hybrid polymer composites. The luffa and carbon fibers are added in the weight percentage of 40/0, 20/20, 25/15, and 15/25 with an epoxy matrix. The fabricated samples are machined as per ASTM standards. The Mechanical tests were done using the UTM machine. The tested samples have shown improvement in mechanical properties with more volume of carbon fiber with luffa fiber. The morphological images of the fractured surface are evaluated on the tensile tested specimens using a scanning electron microscope and various failure mechanisms are highlighted. This hybrid composite could find potential structural applications.